A cross‐linked anti‐TNF‐α aptamer for neutralization of TNF‐α‐induced cutaneous Shwartzman phenomenon: A simple and novel approach for improving aptamers' affinity and efficiency. (12th July 2021) - Mashayekhi, Kazem; Sankian, Mojtaba; Haftcheshmeh, Saeed Mohammadian; Taheri, Ramezan Ali; Hassanpour, Kazem; Farnoosh, Gholamreza
Abstract: To increase the efficiency of aptamers to their targets, a simple and novel method has been developed based on aptamer oligomerization. To this purpose, previously anti‐human TNF‐α aptamer named T1–T4 was trimerized through a trimethyl aconitate core for neutralization of in vitro and in vivo of TNF‐α. At first, 54 mer T1–T4 aptamers with 5′‐NH2 groups were covalently coupled to three ester residues in the trimethyl aconitate. In vitro activity of novel anti‐TNF‐α aptamer and its dissociation constant ( K d ) was done using the L929 cell cytotoxicity assay. In vivo anti‐TNF‐α activity of new oligomerized aptamer was assessed in a mouse model of cutaneous Shwartzman. Anchoring of three T1–T4 aptamers to trimethyl aconitate substituent results in formation of the 162 mer fragment, which was well revealed by gel electrophoresis. In vitro study indicated that the trimerization of T1–T4 aptamer significantly improved its anti‐TNF‐α activity compared to non‐modified aptamers ( P  < 0.0001) from 40% to 60%. The determination of K d showed that trimerization could effectively enhance K d of aptamer from 67 nM to 36 nM. In vivo study showed that trimer aptamer markedly reduced mean scar size from 15.2 ± 1.2 mm to 1.6 ± 0.1 mm ( P <  0.0001), which prevent the formation of skin lesions. In vitro and in vivo studies indicate that trimerization of anti‐TNF‐α aptamer with a novel approach could improve the anti‐TNF‐α activity and therapeutic efficacy. According to our findings, a new anti‐TNF‐α aptamer described here could be considered an appropriate therapeutic agent in treating several inflammatory diseases.